Effects of Plyometric Training on Sprint Running Performance in Boys Aged 9-12 Years - Nobuaki Tottori; Satoshi Fujita (MDPI AG, 2019)
Skilled sprinting is fundamental in many sports, especially to improve athletic performance in youth. This study therefore aimed to investigate the effect of plyometric training on sprint performance in boys aged 9−12 years. Twenty boys were divided into a plyometric training group (n = 9) and a control training group (n = 11). In both groups, participants performed respective training programs once per week for 8 weeks with measurements at baseline and post-intervention. Sprint performance was assessed by 50-m sprint time, sprint velocity, step frequency and step length at 10-m intervals. Jumping performance was assessed using horizontal, vertical and rebound jumps. The plyometric training group showed an improved sprint velocity at 20−30 m, 30−40 m and 40−50 m, and step length at 0−10 m, 20−30 m and 30−40 m (p < 0.05). Furthermore, only the plyometric group showed an increased standing long jump distance and rebound jump performance (p < 0.05). The control group did not show any significant changes in any variable. Our findings suggest that plyometric training in pre-adolescent boys improves sprint velocity and step length at the maximum velocity phase concomitant with increased horizontal and rebound jump performance.